RELEVANSI MODERASI BERAGAMA DALAM MANAJEMEN PENDIDIKAN ISLAM DI INDONESIA: STRATEGI MEMBANGUN KARAKTER TOLERAN DAN INKLUSIF - Wahyu Ningsih, Indah; Supriani, Yuli; Kartika, Ika; Arifudin, Opan (Penerbit Lafadz Jaya, 2025)
Religious moderation is a fundamental principle in Islam that emphasizes balance, justice, tolerance, and the middle path in religious life. In Indonesia’s multicultural and multireligious context, these values are highly relevant to be integrated into the management of Islamic education. This article aims to examine the relevance of religious moderation in strengthening the management system of Islamic education in Indonesia and its role in shaping students' tolerant, inclusive, and civilized character. Using a qualitative approach, the study concludes that wasathiyah values can serve as a strategic foundation in educational planning, curriculum development, teaching methods, and institutional culture. The integration of moderation values into Islamic education management is believed to foster a learning environment that is peaceful, participatory, and adaptive to social diversity, thus producing a generation of Muslims who are both religious and capable of living harmoniously in a pluralistic society.